The shadow house - Downes, Anna (New York : Minotaur Books, 2022)
"Extraordinarily tense and deliciously mysterious, Anna Downes's The Shadow House follows one woman's desperate journey to protect her children at any cost, in a remote place where not everything is as it seems. A HOUSE WITH DEADLY SECRETS. A MOTHER WHO'LL RISK EVERYTHING TO BRING THEM TO LIGHT. Alex, a single mother-of-two, is determined to make a fresh start for her and her children. In an effort to escape her troubled past, she seeks refuge in a rural community. Pine Ridge is idyllic; the surrounding forests are beautiful and the locals welcoming. Mostly. But Alex finds that she may have disturbed barely hidden secrets in her new home. As a chain of bizarre events is set off, events eerily familiar to those who have lived there for years, Alex realizes that she and her family might be in greater danger than ever before. And that the only way to protect them all is to confront the shadows lurking in Pine Ridge"--
Keywords: Single mothers -- Fiction; Country life -- Fiction; Moving, Household -- Fiction; Fictional Work; Psychological fiction; Thrillers (Fiction); Novels